Association of Prenatal Alcohol Exposure With Psychological, Behavioral, and Neurodevelopmental Outcomes in Children From the Adolescent Brain Cognitive Development Study - Lees, Briana (Am J Psychiatry, 2020)
OBJECTIVE: Data on the neurodevelopmental and associated behavioral effects of light to moderate in utero alcohol exposure are limited. This retrospective investigation tested for associations between reported maternal prenatal alcohol use and psychological, behavioral, and neurodevelopmental outcomes in substance-naive youths. METHODS: Participants were 9,719 youths (ages 9.0 to 10.9 years) from the Adolescent Brain Cognitive Development Study. Based on parental reports, 2,518 (25.9%) had been exposed to alcohol in utero. Generalized additive mixed models and multilevel cross-sectional and longitudinal mediation models were used to test whether prenatal alcohol exposure was associated with psychological, behavioral, and cognitive outcomes, and whether differences in brain structure and resting-state functional connectivity partially explained these associations at baseline and 1-year follow-up, after controlling for possible confounding factors. RESULTS: Prenatal alcohol exposure of any severity was associated with greater psychopathology, attention deficits, and impulsiveness, with some effects showing a dose-dependent response. Children with prenatal alcohol exposure, compared with those without, displayed greater cerebral and regional volume and greater regional surface area. Resting-state functional connectivity was largely unaltered in children with in utero exposure. Some of the psychological and behavioral outcomes at baseline and at the 1-year follow-up were partially explained by differences in brain structure among youths who had been exposed to alcohol in utero. CONCLUSIONS: Any alcohol use during pregnancy is associated with subtle yet significant psychological and behavioral effects in children. Women should continue to be advised to abstain from alcohol consumption from conception throughout pregnancy.